Fifty-two-week continuous abstinence rates of smokers being treated with varenicline versus nicotine replacement therapy - Kralikova, Eva; Kmetova, Alexandra; Stepankova, Lenka; Zvolská, Kamila; Davis, Rachel; West, Robert (Addiction, 2013)
BACKGROUND AND AIMS: Cross-study comparisons of effect sizes suggest that varenicline is more effective than nicotine replacement therapy (NRT) in aiding smoking cessation, but evidence from direct comparisons is limited. This study compared biochemically verified 52-week sustained abstinence rates in smokers attending the same clinical service according to whether they used varenicline or NRT in their quit attempt. METHODS: This was a prospective cohort study of 855 smokers attending a large smoking cessation clinic who used their choice of NRT product or varenicline in their quit attempt. All received the same behavioural support programme and chose their medication option (n = 519 varenicline; n = 336 NRT). The primary outcome measure was self-report of 52 weeks' abstinence following the target quit date confirmed by expired air carbon monoxide concentration. Baseline measures included socio-demographic variables, mental health diagnoses, measures of smoking, cigarette dependence and past use of NRT or varenicline. RESULTS: The 52-week abstinence rates were 42.8% versus 31.0% in those using varenicline versus NRT, respectively (P < 0.001). After adjusting for all baseline variables, the odds of remaining abstinent for 52 weeks were 2.03 (95% CI 1.46-2.82), P < 0.001 times higher in those using varenicline than those using NRT. CONCLUSIONS: Smokers in the same behavioural support programme who use varenicline appear to have a greater probability of achieving long-term abstinence than those using their choice of nicotine replacement therapy options, even after adjusting for potentially confounding smoker characteristics.
Keywords: výsledek terapie; Carbon Monoxide; benzazepiny; Male; Smoking Cessation; prevence kouření; dechové testy; způsoby aplikace léků; Nicotinic Agonists; Benzazepines; chinoxaliny; Prospective Studies; mužské pohlaví; Tobacco Use Cessation Devices; Smoking Prevention; Breath Tests; Smoking; Treatment Outcome; nikotinoví agonisté; lidé; Drug Administration Routes; ženské pohlaví; Humans; odvykání kouření; Quinoxalines; Female; prostředky pro ukončení závislosti na tabáku; lidé středního věku; oxid uhelnatý; kouření; Middle Aged; prospektivní studie